Practice of City Visual Identity Design Based on Zhuang Ethnic Minority Rice Farming Culture in Long’an, Guangxi Province: การออกแบบภาพลักษณ์อำเภอหลงอัน มณฑลกว่างซี จากวัฒนธรรมการทำนาข้าว ของชนเผ่าจ้วง - Xu, Xiaoting; Tanyapirom, Sakesan; Suntrayuth, Rasa (Mekong-Salween Civilization Studies Journal, 2025)
The objective of this research was to perform an analytical study on the principles and methods of city visual identity design from 6 associated case studies in order to apply to this type of design that reflected the meanings of Zhuang ethnic minority rice farming culture in Long’an. The research mainly focused on the identity that represented rice farming culture and cultural symbols of Zhuang ethnic minority rice farming culture in Long’an, Guangxi. The methodology relied on documentary research, case study analysis, field research, interviews with experts, questionnaire, and design result assessment. According to the analysis of images/visual identities from different cities, e.g., New York, Hong Kong, Chongqing, Hangzhou, Wuhan, and Guilin using Peirce’s semiotics theory, it was found that there are 3 types of city visual identity design as follows: 1) Symbolic marks: A city visual identity should be simply designed and easy to understand for easy recognition and dissemination; 2) Cultural symbols of an ethnic group/minority: Design must give precedence to the culture of that ethnic group/minority in order to enhance pride in their own culture; and 3) Regional symbols: Design must emphasize regional characteristics in order to create distinctive/unique points from symbols of other cities for publicizing. Furthermore, 3 methods of city visual identity design were also obtained as follows: 1) Branding-based symbol creation: The concept of holistic urban development should be extracted into keywords or the slogan of a city, parallel to displayed symbolic visual images as part of visual identity design; 2) Abstract-based graphic symbol creation: Synthesize visual images of objects that represent the city into abstracts, and create them into new visual symbols; and 3) Imagery-based color symbol creation: Show colors that represent the city as per imagery. Use emotions and feelings of colors and symbolic meanings to convey the meanings of characteristics and spiritual connotations of the city, and then use them as a guideline on creative design. The process of city visual identity design according to brand concept creates such design system as ‘Hometown of the Culture’ using ‘a large stone shovel’ as the graphic symbol, with green and gold as the visual identity color as well as ‘A cow and a bird’ as the mascots to reflect identity and connotations of rice farming culture.